Large desmoplastic fibroma: case report using microvascularized fibula graft for reconstruction - Cleverson Patussi; Laurindo Moacir Sassi; Regiane Benez Bixofis; Paola Andrea Galbiatti Pedruzzi; Alfredo Benjamim Duarte da Silva; Juliana Lucena Schussel (Brazilian Dental Science)
The Desmoplastic Fibroma is a benign rare tumor of fibroblastic origin, representing only 0.03% of benign bone tumors. Displays aggressive behavior and high rates of recurrence, which makes the treatment more aggressive. We report a case of a 11 years-old female, complaining of increased volume in the jaw. The patient had an extensive swelling of the left mandibular body with invasion of the border of the tongue and floor of the mouth at the same side. She had a history of 4 recurrences at the same place. Images exams revealed expansive lesion in body and ramus of the jaw with involvement of soft tissue on the lingual side of the lesion. The treatment was excision of the lesion with extra oral access and reconstruction with microvascularized fibula graft. The patient lies in clinically and radiographic followed for 2 years without recurrence.